Islamic Versus Conventional Stock Market Indices Performance: Empirical Evidence from Turkey - bayram, kamola; Abdullah Othman, Anwar Hasan (IQTISHADIA, 2019)
Rapid growth of Islamic finance in general and Sharī`ah compliant stocks in particular arises the question whether Islamic funds/stocks have a better performance or there is no significant difference with the performance of conventional counterparts. This study has twofold objectives, firstly to compare the performance of Islamic and conventional stock market indices in Turkey, namely KATILIM50 and BIST 100 by using Two-Sample Test of Hypothesis over the period of 15 May 2015 to 31 December 2016.  Secondly, to examine the causal relationship between both stocks markets indices in the short-run using Granger (1969) Causality Test. The findings of parametric Z-test reveals that there is no statistical significant difference between the performance of both indices the KATILIM 50 index and BIST 100 index in Turkey Stock Exchange Market during the time frame of the study.  Further, the Granger Causality findings indicate the absence of causal relationship between the two stock markets indices in the short-run. This suggests that stock markets in Turkey are informationally efficient and non-violated with the Efficient Market Hypothesis with respect to the available information of both indices. The findings of this study therefore will provide useful channel for Muslim investors to fully participate in the Turkish capital market that is Sharī`ah complaint and fulfil their religious belief without sacrificing any financial performance.